Effect of a freeze–thaw cycle on amniotic fluid interleukin-6 concentrations in pregnancies with preterm prelabor rupture of membranes: Implications for the diagnosis of intra-amniotic inflammation - Richard Spacek; Stepanka Bubenikova; Ivana Musilova; Nikola Kuzniciusova; Karolina Janochova; Michaela Kostelkova; Ladislava Pavlikova; Magdalena Holeckova; Marek Lubusky; Ondrej Simetka; Bo Jacobsson; Marian Kacerovsky (PLoS ONE, 2026)
Objective Preterm prelabor rupture of membranes (PPROM) is frequently complicated by intra-amniotic inflammation. Interleukin-6 (IL-6) measured in amniotic fluid is considered the gold-standard biomarker for the diagnosis of this condition; however, diagnostic thresholds have been derived primarily from biobanked samples. It remains unclear whether IL-6 concentrations measured in fresh amniotic fluid are directly comparable with those obtained from previously processed samples. The primary aim of this study was to compare IL-6 concentrations in fresh amniotic fluid samples with those in biobanked samples that had undergone a single freeze–thaw cycle. Method This retrospective study included consecutive singleton pregnancies with PPROM between 24 + 0 and 36 + 6 weeks of gestation. Amniotic fluid samples were collected on admission, prior to the administration of antibiotics and corticosteroids. IL-6 concentrations were measured in both fresh and biobanked (processed) samples using an automated electrochemiluminescence immunoassay. Results The study population comprised 152 women. IL-6 concentrations in fresh and processed samples were strongly correlated (rho = 0.97; p < 0.0001). Bland–Altman analysis demonstrated a systematic bias toward higher concentrations in processed samples, with a mean ratio of 1.2, indicating that processed samples yielded on average approximately 20% higher values than fresh samples. When applying the validated diagnostic threshold of 3,000 pg/mL (established in processed samples) to fresh samples, three false-negative cases were observed. In these cases, intra-amniotic inflammation was present, but IL-6 concentrations in fresh samples were below the threshold despite corresponding processed values ≥ 3,000 pg/mL. Using intra-amniotic inflammation defined by processed samples as the reference, the diagnostic performance of the 3,000 pg/mL threshold applied to fresh samples was as follows: sensitivity 92%, specificity 100%, positive predictive value 100%, and negative predictive value 97%. Conclusions IL-6 concentrations in fresh and processed amniotic fluid samples are highly correlated, but processed samples consistently yield higher values.